Problem solving and data analysis using Minitab a clear and easy guide to six sigma methodology - Khan, Rehman M. (Chichester, West Sussex, U.K. : Wiley, 2013)
"Problem Solving and Data Analysis using Minitab presents example based learning to aid readers in understanding how to use MINITAB 16 for statistical analysis and problem solving"--
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Minitab; Mathematical statistics -- Data processing; Problem solving -- Statistical methods; Six sigma (Quality control standard); Electronic books